Predictive Factors for Access-Site Pain Chronicity after Percutaneous Coronary Intervention via Radial Artery Access - Liuda Brogiene; Giedre Baksyte; Agne Klimaite; Martynas Paliokas; Andrius Macas (Pain Research and Management)
Objectives. The aim of this study is to assess the prevalence and predictive factors for developing chronic access-site (A-S) pain after percutaneous coronary intervention (PCI) via radial artery access. Methods. Data of selected patients (n = 161) who underwent elective PCI were collected prospectively and analysed in 2020. Verbal analogue scale was used to evaluate pain intensity after 12, 24, and 48 h and 3 months after PCI. The univariate logistic regression analysis was used. Results. Pain prevalence decreased from 29% straight after PCI and 54% two hours later to 3.7% following 3 months after procedure. The predictors for A-S pain chronicity are diabetes (OR = 5.77 95% CI (1.07–31.08), p=0.041), hematoma (OR = 6.48, 95% CI (1.06–39.66), p=0.043), A-S hand neuropathy (OR = 19.93 95% CI (1.27–312.32), p=0.033), A-S pain immediately after PCI (OR = 14.60 95% CI (1.63–130.27), p=0.016), after 12 h (OR = 17.2 95% CI (1.60–185.27), p=0.019), 24 h (OR = 48 95% CI (4.87–487), p=0.01), and 48 h (OR = 23.46 95% CI (3.81–144.17), p=0.001), and pain intensity immediately after procedure (OR = 3.30 95% CI (1.65–6.60), p=0.001), after 2 h (OR = 2.56 95% CI (1.15–5.73), p=0.022), after 12 h (OR = 3.02 95% CI (1.70–5.39), p<0.001), after 24 h (OR = 3.58 95% CI (1.90–6.74), p<0.001), and after 48 h (OR = 2.89 95% CI (1.72–4.87), p<0.001). Pain control was performed with Ketoprofen and Ibuprofen as most used NSAIDs. 10 mg of Morphine intravenously was the choice from strong opioids if necessary. Conclusions. The prevalence of chronic A-S pain is 3.7%. Main predictive factors for the A-S pain chronicity are diabetes, hematoma, and persistent pain and pain intensity during 48 h period after PCI.